PENGEMBANGAN INSTRUMEN SOAL PILIHAN GANDA BERBANTU APLIKASI QUIZIZZ MATERI SISTEM PERNAPASAN PADA MANUSIA UNTUK PESERTA DIDIK KELAS VIII SMP - Riza Ardania; Lina Arifah Fitriyah; Nur Kuswanti (Discovery, 2022)
Abstract: The Covid-19 pandemic has caused the evaluation process to be different from before. This is due to the inability to meet face-to-face between teachers and students. One of the supporting applications that can be used is quizizz. This study aims to (1) describe the process of developing multiple-choice instruments with the help of quizizz applicaton. (2) describe the product developed after the validation process. This research is a development research using the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The question instrument developed consists of 20 multiple choice questions and is equipped with operating instructions for quizizz application. The development data obtained were analyzed descriptively and quantitatively. The results of the development of the multiple-choice instrument with the help of quizizz application after validation showed that the multiple-choice instrument was stated to be very good with a percentage of 99.3%. Based on the results of the expert test, the multiple-choice instrument assisted by theapplication quizizz can be applied to students. Keywords​: ​​development, multiple choice question, quizizz.